Risk factors for higher anti-HCV positivity in a border city in southern Turkey with unique population characteristics - Birol ÖZER; Gülşah SEYDAOĞLU; Akatlı Kürşat ÖZŞAHİN and Hakan DEMİRHİNDİ (Turkish Journal of Gastroenterology, 2019)
-